2014
DOI: 10.1111/hiv.12127
|View full text |Cite
|
Sign up to set email alerts
|

Multiple hepatitis C virus (HCV) reinfections in HIV‐positive men who have sex with men: no influence of HCV genotype switch or interleukin‐28B genotype on spontaneous clearance

Abstract: ObjectivesThe incidence of sexually transmitted hepatitis C virus (HCV) reinfection is on the rise in HIV-infected men who have sex with men (MSM). Data on natural history of acute hepatitis C and possible factors associated with spontaneous clearance are limited. The aim of this study was to analyse the outcome of HCV reinfections in HIV-positive MSM. MethodsA retrospective analysis was carried out on patients with more than one sexually acquired HCV infection who were diagnosed at four major German HIV and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
28
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 31 publications
(35 reference statements)
3
28
0
2
Order By: Relevance
“…In addition, coinfection with two or more HCV strains of different genotypes or subtypes is a common finding in some high-risk groups. Researchers who performed several studies in persons who inject drugs (PWID) and among men who have sex with men (MSM) have reported the simultaneous presence of two or more HCV subtypes in 25% to 39% of incident infections (16)(17)(18)(19). Taken together, the findings of the subtype-specific response to different classes of DAA and of the frequency of multiple infections among groups with the highest incidence and prevalence of HCV infection make accurate HCV subtyping, including detection of mixed infections, an essential tool to optimize current and future treatment regimens.…”
mentioning
confidence: 99%
“…In addition, coinfection with two or more HCV strains of different genotypes or subtypes is a common finding in some high-risk groups. Researchers who performed several studies in persons who inject drugs (PWID) and among men who have sex with men (MSM) have reported the simultaneous presence of two or more HCV subtypes in 25% to 39% of incident infections (16)(17)(18)(19). Taken together, the findings of the subtype-specific response to different classes of DAA and of the frequency of multiple infections among groups with the highest incidence and prevalence of HCV infection make accurate HCV subtyping, including detection of mixed infections, an essential tool to optimize current and future treatment regimens.…”
mentioning
confidence: 99%
“…The lack of protective immunity HCV reinfection after spontaneous clearance of the virus has been observed in chimpanzees [101,102] and in humans [7,[103][104][105][106][107][108][109][110][111][112][113][114]. As reviewed elsewhere [115], some of these studies have demonstrated evidence of an augmented HCV-specific immune response following reinfection compared to after primary infection, suggesting that some immunological control may develop after repeated exposure to the virus.…”
Section: Hcv Reinfection In High-risk Groupsmentioning
confidence: 99%
“…Yet despite these outcomes the epidemic has continued unabated (5, 10). In the presence of maintained risk behavior, HCV reinfections have been described in PWID and MSM who either cleared their initial infection spontaneously or were successfully treated with interferon-based therapies (17)(18)(19)(20). In a recent meta-analysis of 61 studies, the five-year risk of HCV reinfection in HIV infected MSM was as high as 15% and higher than in studies on PWID (21).…”
mentioning
confidence: 99%